Workplace Nutrition Interventions: A Systematic Review of Their Effectiveness - Risti Rosmiati; Nila Reswari Haryana; Hardi Firmansyah; Muhammad Edwin Fransiari (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Workplace nutrition interventions have emerged as a pivotal strategy for enhancing employee health by addressing dietary behaviors and reducing the risk of non-communicable diseases. This systematic review evaluates the effectiveness of workplace-based nutrition interventions in improving nutritional outcomes and health indicators among employees. Methods: Using the PRISMA framework, a comprehensive search was conducted across PubMed, ScienceDirect, Scopus, and Google Scholar for studies published between 2020 and 2024. Eligible studies included randomized controlled trials (RCTs) and quasi-experimental designs targeting workplace-based nutrition interventions. A total of 10 studies met the inclusion criteria and were systematically analyzed for outcomes related to dietary behavior, physical activity, and health indicators. Risk of bias assessments were performed to ensure the validity of findings. Results: The findings revealed that dietary interventions, particularly those emphasizing adherence to structured diets like the Mediterranean diet, consistently led to significant improvements in health markers, including reductions in LDL cholesterol and body fat percentage. Interventions combining dietary modifications with physical activity yielded comprehensive benefits, such as weight loss and improved dietary adherence. However, variability in study designs, sample sizes, and contextual factors limited the generalizability of results. Many studies lacked follow-up data to assess the long-term sustainability of health outcomes. Conclusion: Workplace nutrition interventions promote employee health, especially when combining dietary and physical activity components. However, challenges such as methodological heterogeneity, short-term focus, and limited exploration of demographic and contextual factors must be addressed. Future research should prioritize standardized methodologies, conduct longitudinal assessments, and implement tailored interventions that consider workforce diversity and workplace culture. These findings provide actionable insights for policymakers and employers seeking to design sustainable workplace health initiatives that enhance employee well-being and organizational productivity.